T$_{(1,2)^\star \text{-} ψ}$-spaces - S. Saranya; N. Seenivasagan; O. Ravi (International Journal of Mathematics And its Applications, 2017)
In this paper, we introduce the notions called T$_{(1,2)^\star \text{-} ψ}$-spaces, gT$_{(1,2)^\star \text{-} ψ}$-spaces and $α$T$_{(1,2)^\star \text{-} ψ}$-spaces and obtain their properties and characterizations.